European Stroke Organisation – European Society for Minimally Invasive Neurological Therapy expedited recommendation on indication for intravenous thrombolysis before mechanical thrombectomy in patients with acute ischaemic stroke and anterior circulation large vessel occlusion. (March 2022) - Turc, Guillaume; Tsivgoulis, Georgios; Audebert, Heinrich J.; Boogaarts, Hieronymus; Bhogal, Pervinder; De Marchis, Gian Marco; Fonseca, Ana Catarina; Khatri, Pooja; Mazighi, Mikaël; Pérez de la Ossa, Natalia; Schellinger, Peter D.; Strbian, Daniel; et al.
Six randomized controlled clinical trials have assessed whether mechanical thrombectomy (MT) alone is non-inferior to intravenous thrombolysis (IVT) plus MT within 4.5 hours of symptom onset in patients with anterior circulation large vessel occlusion (LVO) ischaemic stroke and no contraindication to IVT. An expedited recommendation process was initiated by the European Stroke Organisation (ESO) and conducted with the European Society of Minimally Invasive Neurological Therapy (ESMINT) according to ESO standard operating procedure based on the GRADE system. We identified two relevant Population, Intervention, Comparator, Outcome (PICO) questions, performed systematic reviews and meta-analyses of the literature, assessed the quality of the available evidence and wrote evidence-based recommendations. Expert opinion was provided if insufficient evidence was available to provide recommendations based on the GRADE approach. For stroke patients with anterior circulation LVO directly admitted to a MT-capable centre ('mothership') within 4.5 hours of symptom onset and eligible for both treatments, we recommend IVT plus MT over MT alone (moderate evidence, strong recommendation). MT should not prevent the initiation of IVT, nor should IVT delay MT. In stroke patients with anterior circulation LVO admitted to a centre without MT facilities and eligible for IVT ≤4.5 hrs and MT, we recommend IVT followed by rapid transfer to a MT capable-centre ('drip-and-ship') in preference to omitting IVT (low evidence, strong recommendation). Expert consensus statements on ischaemic stroke on awakening from sleep are also provided. Patients with anterior circulation LVO stroke should receive IVT in addition to MT if they have no contraindications to either treatment.